Beneficial effects of an Andrographis paniculata extract and andrographolide on cognitive functions in streptozotocin-induced diabetic rats - Thakur A.K.; Rai G.; Chatterjee S.S.; Kumar V. (My University, 2025)
Context Andrographolide containing Andrographis paniculata (Burm. F.) Wall. Ex Nees (Acanthaceae) extracts is often used for treatments of diabetes and other inflammatory disorders commonly accompanying cognitive and other psychiatric disorders. Objective To compare the efficacies of a standardised A. paniculata extract (AP) and pure andrographolide on cognitive functions, oxidative stress and cholinergic function in diabetic rats. Materials and methods Streptozotocin-induced diabetic Charles Foster albino rats treated orally with a hydro-methanolic A. paniculata leaf extract (50, 100 and 200 mg/kg/day), or with pure andrographolide (15, 30 and 60 mg/kg/day) for 10 consecutive days, were subjected to Morris water maze test. After the test, acetylcholinesterase, superoxide dismutase (SOD), and catalase (CAT) activities and lipid peroxidation (LPO) in brain tissues were assessed. Results Acetylcholinesterase activity in pre-frontal cortex and hippocampus of diabetic rats was 2.1 and 2.6 times higher compared to nondiabetic rats. LPO was 1.6 times higher and decreased SOD (56.3%) and CAT (44.9%) activities in pre-frontal cortex of diabetic rats compared to nondiabetic rats. AP or andrographolide treatments dose dependently attenuated cognitive deficits, reduced acetylcholinesterase activity, oxidative stress, improved diabetic hyperglycemia and insulin deficiency. All observed effects of AP were quantitatively almost equal to those expected from its analytically quantified andrographolide content. Discussion and conclusion Reported observations are the very first ones suggesting beneficial effects of andrographolide against diabetes associated cognitive deficits, increased acetylcholinesterase activity and deteriorated antioxidative status. Efforts to exploit A. paniculata extracts enriched in andrographolide as preventive measures against such disorders can be warranted. © 2016 Informa UK Limited, trading as Taylor & Francis Group.